NLRX1 ligand, docosahexaenoic acid, ameliorates LPS-induced inflammatory hyperalgesia by decreasing TRAF6/IKK/IkB-a/NF-kB signaling pathway activity: DHA ameliorates LPS-induced inflammatory hyperalgesia - Yilmaz, Dilsah Ezgi; Senol, Sefika Pinar; Temiz-Resitoglu, Meryem; Sahan-Firat, Seyhan; Tunctan, Bahar (Cellular and Molecular Biology, 2023)
The nucleotide-binding oligomerization domain-like receptor X1 (NLRX1) has been associated with various anti-inflammatory mechanisms. We investigated whether the NLRX1 ligand docosahexaenoic acid (DHA) ameliorates lipopolysaccharide (LPS)-induced inflammatory hyperalgesia by interacting with tumor necrosis factor receptor-associated factor 6 (TRAF6)/inhibitor of kB (IkB) kinase (IKK)/IkB-a/nuclear factor-κB (NF-κB) signaling pathway in the central nervous system. Reaction time to thermal stimuli within 30 seconds was measured in male mice injected with saline, lipopolysaccharide (LPS), and/or DHA after 6 hours using the hot plate test. Co-immunoprecipitation and immunoblotting studies were performed to determine the activation of the TRAF6/IKK/IkB-a/NF-kB pathway in the brains and spinal cords of animals. Latency to the thermal stimulus was reduced by 30% in LPS-injected endotoxemic mice compared with saline-injected mice. Treatment with DHA significantly improved latency compared with endotoxemic mice. In the brain and spinal cord of LPS-injected mice, treatment with DHA also prevented the increase in the expression and/or activity of (1) IKKa/IKKβ, IKKg, and K63 U in the NLRX1-immunoprecipitated tissues, (2) IKKa/IKKβ, K63 U, and K48 U in the IKKg-immunoprecipitated tissues, and (3) IkB-α, NF-kB p65, and interleukin-1β associated with decreased IkB-α expression. These findings suggest that inhibition of IKK/IkB-a/NF-kB signaling by dissociation of NLRX1 from TRAF6 in response to LPS treatment contributes to the protective effect of DHA against inflammatory hyperalgesia.